Ground Subsidence Evolution from 1000 m Deep Mining: A Case Study in Fengfeng Mining Area. (27th September 2021) - Yan, Yueguan; Li, Ming; Liu, Jibo; Yan, Weitao; Zhang, Jinman; Zhou, Bang
Abstract : The mining of coal resources in eastern China has entered the stage of deep mining, and many mines have reached the depth of 1000 meters. Different from shallow and moderate depth mining, the temporal and spatial evolution regulation of surface movement and deformation under deep mining has its particularity. Combining with the geological and mining conditions of Fengfeng mining area, this paper systematically studies the characteristics of surface movement under the condition of shallow, moderate, and near kilometer mining depth. By means of field measurement, InSAR monitoring, we get the subsidence data under different mining depth and get the relevant subsidence parameters by inversion. Through comparative analysis, the special law of subsidence under the mining depth of 1000 meters is obtained. The results show that under the condition of nearly 1000 meters mining depth, the surface movement and deformation have the characteristics of large displacement angle, small displacement deformation value, and large main influence radius. The regulation of small proportion of active period of maximum subsidence point, gentle shape of surface movement basin, and low mining adequacy are obtained. The research results provide technical references for deep mining under buildings, railways, and water bodies and provide basis and reference for scientific mining and safe recovery of coal pillars in kilometer deep mine.